Atmospheric Hydroxyl Radical Reaction Rate Coefficient and Total Environmental Lifetime of α-Endosulfan - Alarcon, Paulo C; Kitanovski, Zoran; Padervand, Mohsen; Pöschl, Ulrich; Lammel, Gerhard; Zetzsch, Cornelius (Environmental science & technology, 2023)
Endosulfan is a persistent organochlorine pesticide that was globally distributed before it was banned and continues to cycle in the Earth system. The chemical kinetics of the gas-phase reaction of α-endosulfan with the hydroxyl radical (OH) was studied by means of pulsed vacuum UV flash photolysis and time-resolved resonance fluorescence (FP-RF) as a function of temperature in the range of 348-395 K and led to a second-order rate coefficient kOH = 5.8 × 10-11 exp(-1960K/T) cm3 s-1 with an uncertainty range of 7 × 10-12 exp(-1210K/T) to 4 × 10-10 exp(-2710K/T) cm3 s-1. This corresponds to an estimated photochemical atmospheric half-life in the range of 3-12 months, which is much longer than previously assumed (days to weeks). Comparing the atmospheric concentrations observed after the global ban of endosulfan with environmental multimedia model predictions, we find that photochemical degradation in the atmosphere is slower than the model-estimated biodegradation in soil or water and that the latter limits the total environmental lifetime of endosulfan. We conclude that the lifetimes typically assumed for soil and aquatic systems are likely underestimated and should be revisited, in particular, for temperate and warm climates.
Keywords: organochlorine pesticide; Pesticides; Endosulfan; Temperature; hydroxylový radikál; Kinetics; Soil; půda; multicompartmental distribution; endosulfan; teplota; pesticidy; kinetika; Hydroxyl Radical; hydroxyl radical; persistent organic pollutant; reaction kinetics